2004
DOI: 10.1111/j.1439-0396.2003.00474.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of blood parameters during weight loss in experimental obese Beagle dogs

Abstract: The effects of weight loss on hormonal and biochemical blood parameters were measured monthly [carnitine, creatinine, urea, free T4 (fT4), total T4 (TT4), plasma alkaline phosphatases (ALP), aspartate aminotransferase (AST), alanine aminotransferase (ALT), potassium and total proteins] or bimonthly [cholesterol, triglycerides, non-esterified fatty acids (NEFA), insulin-like growth factor I (IGF-I), glucose, insulin] in eight obese Beagles dogs fed either a high protein dry diet, DP (crude protein 47.5%, on dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
33
1
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 10 publications
6
33
1
7
Order By: Relevance
“…Measurement of GFR before and after weight loss might have helped to differentiate between these possibilities. The decrease in serum creatinine concentration is contradictory to previous studies in obese dogs, whereby increased serum creatinine concentration has been documented following weight loss . This decrease could be the result of loss of muscle mass during weight management.…”
Section: Discussioncontrasting
confidence: 91%
“…Measurement of GFR before and after weight loss might have helped to differentiate between these possibilities. The decrease in serum creatinine concentration is contradictory to previous studies in obese dogs, whereby increased serum creatinine concentration has been documented following weight loss . This decrease could be the result of loss of muscle mass during weight management.…”
Section: Discussioncontrasting
confidence: 91%
“…While not statistically significant, dogs consuming beans showed the largest change at 2 weeks whereas the decrease in the control group was similar between 2 and 4 weeks. This finding demonstrated that serum cholesterol reduction may be an early biomarker for a metabolic response to bean intake and weight loss wherein previous reports in dogs showed decreased serum cholesterol after 60 days [53], 90 days [50], and after the full amount of time required to reach ideal weight [54,55]. Furthermore, TG, HDL and LDL were reduced in at least one of the bean diet groups, a finding consistent in human studies [32], with the exception of HDL which has been shown to increase in humans after bean consumption [56].…”
Section: Discussionmentioning
confidence: 55%
“…ALP was significantly reduced in dogs consuming black beans (P=0.01) and had a decreasing trend in the navy bean group (P=0.08). AST levels have not previously been shown to change with weight loss in dogs [55], however was significantly decreased in the control group (P<0.01). Bilirubin, while not elevated in overweight dogs [50], has been shown to be reduced during weight loss with specific diets [53] as was observed in the control group.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…9,[47][48][49][50] In obese dogs, decreases in serum triglyceride, cholesterol and leptin concentrations during weight loss are associated with a decrease in insulin resistance. 9,[47][48][49][50] In obese dogs, decreases in serum triglyceride, cholesterol and leptin concentrations during weight loss are associated with a decrease in insulin resistance.…”
Section: Discussionmentioning
confidence: 99%